Implementation of Character Education from the Perspective of Philosophy of Science: Science, Ethics, and Morals as the Foundation of Holistic Education Value - Muhammad Isro' Hidayatullah; Retna Ayu Rachmawati; A Farmozi Zain; Muslehudin Muslehudin; Rusnan Hadi (Yayasan Siti Widhatul Faeha Salahudin Syawal, 2025)
The understanding of ethics and morality in education is an inseparable element in the application of knowledge. On the other hand, the philosophy of science serves as a discipline that fosters essential life values such as ethics and morality, examining the nature and purpose of knowledge as well as its practical applications. The aim of this article is to analyze how the value of knowledge utility can contribute to character development among students in educational settings. This study employs a qualitative research method with a literature review design. The findings of this study indicate that the integration of ethics, morality, and the utilitarian value of knowledge, along with their implementation in character education and a holistic approach, constitutes a fundamental foundation in shaping well-rounded, knowledgeable, and dignified individuals. Therefore, the synergy between ethics, morality, and knowledge stands as a key pillar in achieving transformative and sustainable education.